Strategi Manajemen Informasi Iklan Layanan Masyarakat Keluarga Berencana (Studi Kasus di Dinas Pengendalian Penduduk, Pemberdayaan Perempuan dan Perlindungan Anak Kota Surabaya) - Rahmad Abadi Santoso (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
This study aims to identify and explore the information management strategy of public service advertisements about Family Planning carried out by the Department of Population Control, Women's Empowerment, and Child Protection (DP5A) of Surabaya City. This study focuses on information management strategies for Public Service Advertisements about the Family Planning program and the latest advertisements of the BKKBN about "The Importance of Independent Family Planning in a Pandemic", where BKKBN urges the public, especially couples of childbearing age to delay pregnancy in the Covid-19 pandemic era. This research was conducted at the DP5A of Surabaya City using a descriptive method, a qualitative approach. The data collection technique in this study used interviews, observations, and documentation conducted by researchers to leaders, staff employees, IMP cadres, and target communities in the Public Service Advertising family planning program in Surabaya City. The results of this study indicate that the information management strategy of Public Service Advertising of Family Planning in the DP5A of Surabaya City is made in the form of images and videos which are disseminated by utilizing the Website and Social Media such as Instagram and Youtube. Furthermore, the DP5A of Surabaya City also utilizes IMP cadres owned by DP5A of Surabaya City to reach out to people who are not active on electronic media. In addition, the production of advertising materials at the DP5A of Surabaya City begins with instructions given by the Head of the Division which is then followed up by the Chair of Sie and the Field Staff until the advertisement is declared ready to be distributed to the target community. After the advertisement is declared ready to be distributed, the Head of Division and the Head of Sie approve and determine the strategy for distributing the advertisement so that it can be well received by the target community, and after that, the IT staff disseminates the advertisement following the orders and directions given. In this era of the COVID-19 pandemic, the BKKBN provided information and messages, in particular, in the form of a video about "The Importance of Independent Family Planning in a Time of Pandemic", where this was done because it was feared that due to restrictions on social activities in the community, many female reproductive age women experienced unplanned pregnancies that resulted in pregnancy loss that will increase the safety risk to mother and child. This research is limited to a discussion of information management strategies for public service advertisements about family planning in DP5A Surabaya City so that further research needs to reveal the effectiveness of PSAs conducted by DP5A Surabaya City to know how effective it is.